ARABIC LEARNING BASED ON MULTIPLE INTELLIGENCE AT MARKAZ ARABIYA - Moh Sholeh Afyuddin; Rena Rafidania; Ivan Fajriyanur (Thariqah Ilmiah: Jurnal ilmu-ilmu kependidikan & Bahasa Arab, 2023)
Learning aims to influence students, which is known by changes in behavior, knowledge, and mastery of certain competencies. Learning in a group cannot be avoided from the individual differences of the students. There are several psychological theories that studied the individual differences of students, including the theory of multiple intelligences. One of the educational institutions that apply the concept of multiple intelligences is Markaz Arabiya for Arabic Language. The concept of multiple intelligences is able to classify individual tendencies, so that it can accommodate the intelligence of students in developing Arabic language skills. The research problem is about how is the learning Arabic based on multiple intelligences at Markaz Arabiya for Arabic Language? This research is a qualitative research with descriptive analysis type and uses observation, interviews, and documentation as data collection techniques. The data analysis uses reduction, presentation, and conclusions. The results and findings of this study state that Arabic language learning based on multiple intellegencies at Markaz Arabiya can be seen in integration with four main learning activities: 1) interviews and observations of new students at the beginning of learning, in order to identify their type of intelligence, 2) planning made by identifying certain types of intelligence that can be applied in learning activities, 3) the learning process that uses various methods and student-centered with the principles of learning by doing, and 4) evaluation through written tests to measure stundets’ knowledge and skills tests to measure the ability to apply their knowledge in certain tasks. Several types of intelligence appear to be integrated in a series of learning processes, such as linguistic intelligence, mathematical logic, spatial, musical, kinesthetic, interpersonal, intrapersonal and naturalist intelligence. However, among those the several intelligences, linguistic intelligence, mathematical logic, kinesthetic and interpersonal intelligence, are the most dominant intelligences.